Inclined slot cooling of the pressure side rims of squealer tips - Vieira, JAC; Coull, J; Ireland, P (Global Power and Propulsion Society, 2022)
The blade tip is a particularly critical component of the high pressure turbine because the hot gas leaking over it causes a loss of efficiency and degrades the blade. This tip degradation is often a limiting factor of engine life. Squealer designs tend to have high efficiency, but the pressure side rims are particularly vulnerable due to their large surface area and the difficulties of shielding them from hot overtip leakage flow. This paper considers a new approach to cooling the pressure side rim using an inclined slot inside a recessed step. Compared to conventional cooling strategies, in which coolant is provided by multiple cylindrical holes, the slot feature improves cooling effectiveness by more than 50% in key regions of the pressure side rim, whilst also allowing reduction in coolant mass flow. The concept design is developed using a combination of Computational Fluid Dynamics (CFD) calculations and experiments on a linear cascade with representative Mach and Reynolds numbers.